The Effects of Hormonal Factor on the Degree of Acne Vulgaris Severity - Alarik L., Albertus; Indiastuti, Danti Nur; Astari, Linda; Setyaningrum, Trisniartami (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2023)
Background: Acne vulgaris is a disease in the form of chronic inflammation of the pilosebaceous follicles with multifactorial causes. Acne vulgaris is a very common skin disease with a prevalence of 85%  in the age range of 18-25 years. There are aggravating factors that can exacerbate acne vulgaris, including hormonal factors. However, the study about how strong the effects of hormonal factors and on acne severity is really limited. Purpose: The objective of this research is to determine how strong hormonal factors contribute on the severity of acne vulgaris. Methods: This was a cross-sectional retrospective study using secondary data obtained from 199 patients at the Dermatology and Venereology Outpatient Unit of RSUD Dr. Soetomo from January- December 2019. The data were analyzed using SPSS with regression analysis.Result: Hormonal factors significantly influenced the degree of acne vulgaris severity (P-value=0.030). Based on the logistic regression model, it can be found that hormonal factors influence the degree of acne vulgaris by 70% Conclusion: The effect of hormonal factors on the severity of acne vulgaris is 70%.